Analisis Optimalisasi Waktu Proses Kerja pada Divisi Welding Menggunakan Metode Jalur Kritis - Mayrosa, Indila; Kusuma, Harun Indra; Rahmawati, Dewi; Rizki, Yulizan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the optimization of work process time in the welding division using the Critical Path Method (CPM). This method is used to identify the critical path and calculate the slack variable for each production activity. The data used are the sequence of activities, dependency relationships, and production process time in 2024. The analysis process is carried out through the preparation of a network diagram, forward pass and backward pass calculations, and determining the slack value. The results show that the critical path is found in the series of activities A–B–C–D–E–F–G–H with a total duration of 17 minutes. All activities have a slack value of 0, so any delay has the potential to delay the entire process. These findings confirm that the production process in the welding division has been running optimally. The company is advised to maintain the existing work pattern and ensure the appropriate duration of each activity to maintain production efficiency.